2011
DOI: 10.1007/s10157-011-0565-3
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain after 20 years of age is associated with prevalence of chronic kidney disease

Abstract: Weight gain after 20 years of age is associated with CKD among Japanese, even those without metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
(31 reference statements)
1
25
0
Order By: Relevance
“…An increase in weight by more than 1 kilogram / day suggests fluid retention (20) . A study showed a significant association between age and weight gain and identified an average age of 59 years (27) , which is consistent with this study.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in weight by more than 1 kilogram / day suggests fluid retention (20) . A study showed a significant association between age and weight gain and identified an average age of 59 years (27) , which is consistent with this study.…”
Section: Discussionsupporting
confidence: 92%
“…), as well as a risk factor for progression of chronic kidney disease (CKD) (Wakasugi et al . ). Diseases with multiple complications such as CKD are often managed with an integrated, multi‐disciplinary approach.…”
Section: Discussionmentioning
confidence: 97%
“…The SHC has been described elsewhere [14,15]. Briefly, the SHC is a new health-care strategy aimed at early diagnosis and intervention for metabolic syndrome, and was initiated by the Japanese government in 2008.…”
Section: Methodsmentioning
confidence: 99%